Tourism development, governance and sustainability in the Bahamas - Rolle, Sophia; Minnis, Jessica; Bethell-Bennett, Ian (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book focuses on the complex issues of tourism development, governance and sustainability in the long-standing popular island destination, The Bahamas, where tourism remains one of the primary fiscal industries. The book achieves this by looking at the impacts of mass tourism development from social, economic and environmental perspectives, panarchy and resilience, assessing sustainability, moving towards a blue economy, impacts of climate change and innovative alternative tourism offerings to ensure sustainable tourism - a welcomed but challenging essential contemporary focus of the tourism industry. It further looks at how development, governance and sustainability come together in the aftermath of a recent natural disaster, hurricane Dorian, which proved to be a strong catalyst for action, innovation and change in The Bahamas. Given the complexity of these key concepts and The Bahamas as an established popular tourism destination archipelago which relies so heavily on the industry, this book offers significant insight for other tourism regions and will therefore be essential reading for upper-level students and academics in the field of Tourism research"--
OCLC-licensed vendor bibliographic record.
Keywords: Tourism -- Bahamas; Tourism -- Government policy -- Bahamas; Sustainable tourism -- Bahamas; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism